2010
DOI: 10.4314/ijhr.v1i4.55381
|View full text |Cite
|
Sign up to set email alerts
|

Sustained delivery of propranolol by using multiparticulate gastroretentive drug delivery system

Abstract: an online international journal allowing free unlimited access to abstract and full-text of published articles. The journal is devoted to the promotion of health sciences and related disciplines (including medicine, pharmacy, nursing, biotechnology, cell and molecular biology, and related engineering fields). It seeks particularly (but not exclusively) to encourage multidisciplinary research and collaboration among scientists, the industry and the healthcare professionals. It will also provide an international… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
(11 reference statements)
0
1
0
Order By: Relevance
“…As a result, the dosage form is retained in stomach for a long period of time. These systems may be named as "plug typesystem", since they exhibit tendency to remain logged at the pyloric sphincter (Fursule et al, 2008)Various types of floating drug delivery systems are shown in Table 3.…”
Section: Swelling and Expanding Systemsmentioning
confidence: 99%
“…As a result, the dosage form is retained in stomach for a long period of time. These systems may be named as "plug typesystem", since they exhibit tendency to remain logged at the pyloric sphincter (Fursule et al, 2008)Various types of floating drug delivery systems are shown in Table 3.…”
Section: Swelling and Expanding Systemsmentioning
confidence: 99%